The Nuclear Orphan Receptor NR2F6 Promotes Hepatic Steatosis through Upregulation of Fatty Acid Transporter CD36 - Zhou, Bing (Adv Sci (Weinh), 2020)
Nuclear receptors (NRs) are a superfamily of transcription factors which sense hormonal signals or nutrients to regulate various biological events, including development, reproduction, and metabolism. Here, this study identifies nuclear receptor subfamily 2, group F, member 6 (NR2F6), as an important regulator of hepatic triglyceride (TG) homeostasis and causal factor in the development of non‐alcoholic fatty liver disease (NAFLD). Adeno‐associated virus (AAV)‐mediated overexpression of NR2F6 in the liver promotes TG accumulation in lean mice, while hepatic‐specific suppression of NR2F6 improves obesity‐associated hepatosteatosis, insulin resistance, and methionine and choline‐deficient (MCD) diet‐induced non‐alcoholic steatohepatitis (NASH). Mechanistically, the fatty acid translocase CD36 is identified as a transcriptional target of NR2F6 to mediate its steatotic role. NR2F6 is able to bind directly onto the CD36 promoter region in hepatocytes and increases the enrichment of nuclear receptor coactivator 1 (SRC‐1) and histone acetylation at its promoter. Of pathophysiological significance, NR2F6 is significantly upregulated in the livers of obese mice and NAFLD patients. Moreover, treatment with metformin decreases NR2F6 expression in obese mice, resulting in suppression of CD36 and reduced hepatic TG contents. Therefore, these results provide evidence for an unpredicted role of NR2F6 that contributes to liver steatosis and suggest that NR2F6 antagonists may present a therapeutic strategy for reversing or treating NAFLD/NASH pathogenesis.